Infective endocarditis in the colombian caribbean region: clinical profile, microbiological insights, and risk factors for mortality (2023)
Infective endocarditis (IE) is defined as the infectious and inflammatory process of the heart’s internal structures. It can be caused by a broad group of bacteria and, rarely, fungi, with potentially life-threatening consequences. Objective: To profile bacterial resistance and identify mortality risk factors in IE patients. Methods: This crosssectional study included clinically diagnosed IE patients. Sociodemographic, comorbidity, clinical, and microbiological data were recorded. Descriptive analyses, Chi-Square/Fisher’s exact tests, and Student’s t-tests examined variables in relation to IE outcomes (survival vs. mortality). Multivariate logistic regression calculated odds ratios and confidence intervals. Results: We enrolled 39 patients (mean age 51 ± 19.5 years, 54 % male). Common comorbidities included acute kidney injury (AKI) (46 %), heart failure (26 %), and ischemic stroke (21 %). Deceased patients had higher rates of fatigue (p=0.03), lower limb edema (p=0.01), and AKI (p=0.01) than survivors. Fifteen (38 %) patients had positive cultures; Staphylococcus aureus predominated in survivors (13 %) and deceased (13 %) patients (p=0.06). Multi-drug-resistant bacteria were found in six (15 %) patients, and one (2.6 %) had Extensively Drug-Resistant bacteria. Multivariate Logistic Regression indicated that lower limb edema (OR 8.6, 95 % CI 1.5–49, p=0.01), and AKI (OR 7.8, 95 % CI 1.65–37.2, p=0.01) increased mortality risk in IE patients. Conclusion: In this study, lower limb edema and AKI were significant predictors of mortality in IE patients, emphasizing their clinical importance in IE progression and resolution. Further research should explore additional variables and risk factors to enhance our ability to predict and manage outcomes in this population.